BEYOND RELIGIOSITY: A NARRATIVE REVIEW OF THE MULTIFACETED FACTORS INFLUENCING ISLAMIC FINTECH ADOPTION IN SOUTHEAST ASIA - Hussin, Nurul Liyana; Yahaya, Muhamad Hasif; Wan Jusoh, Wan Noor Hazlina (Jurnal ’Ulwan, 2025)
This narrative review explores the multifaceted drivers and barriers influencing the adoption of Islamic fintech services across Southeast Asia with integrates behavioural theories such as Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT) to explain adoption patterns, findings reveal that adoption is shaped by religiosity, trust, perceived risk and facilitating conditions such as digital infrastructure and regulatory frameworks. The findings indicate that while Shariah compliance and religiosity remain important foundations, adoption decisions are increasingly shaped by trust, perceived risk and facilitating conditions such as digital infrastructure and regulatory frameworks. Technological applications including blockchain, smart contracts and artificial intelligence demonstrate significant potential to enhance transparency, efficiency and Shariah governance in Islamic financial services while digital Islamic social finance initiatives contribute to financial inclusion. Nevertheless, persistent challenges remain, particularly inconsistencies in Shariah governance, cybersecurity risks and varying levels of consumer literacy across countries. This paper provides a holistic synthesis of Islamic fintech adoption in Southeast Asia and offers insights for academics, policymakers and industry practitioners seeking to foster sustainable and trustworthy Islamic digital finance ecosystems.